The role of Problem Sections Established in the structure of the Polish Society of Allergology - Brucka-Stempkowska, Monika (Polish Journal of Public Health, 2012)
Polish Society of Allergology (PTA) was founded during the Conference of Founding Members of PTA on November 15, 1982 in Bydgoszcz and is the continuation of the existing since 1965 Section of Allergology at Polish Medical Doctors’ Society. In years 1982-1985 PTA started the organization of regional sections, at the time calling into existence 11 of them with the total number of 440 members. They included the sections of: Białystok, Bydgoszcz, Gdańsk, Krakow, Lublin, Łódź, Poznań, Rzeszów, Silesian, Szczecin and Warsaw. With time the number of new sections increased. Until 1991 there was created Wrocław Section, and on November 15, 1994 the thirteenth and the last section of PTA the Olsztyn section came into existence. Currently the society has 2000 members, its regional structure being composed of 13 Regional Departments mentioned above and 8 Problem Sections: Oculist Section, Pediatric Section, Dermatological Section, Laryngological Section, Young Allergologists’ Section, Clinical-Immunological Section, Specific-Immunotherapy Section and Allergy-for-Nutrition Section. Besides, many of the Society’s members are specialists of various fields, gaining successes both in educational and scientific-research areas.